Institutional factors, corporate governance attributes and sustainability initiatives of Nigerian listed firms: The moderating effect of environmental policy - Kumo, Usman Ahmed (2024)
Sustainability Initiatives (SI), which encompass economic, environmental, social, and governance aspects, have gained prominence due to growing stakeholder interest and are closely related to Corporate Social Responsibility (CSR) reporting. The purpose of this study is to examine the relationship between institutional factors Economic Constraints and Competition (COMP), Governance Attributes of Board Size (BSZE), Board Independence (BOIND), Board Gender Diversity (BGD) and Board CSR Committee (BCSRC)) and SI, and to investigate the moderating effect of Environmental Policy (ENVP) on the relationship between governance attributes and SI on the financial and non-financial listed firms from 2016 to 2021. Data were collected from the companies assessed and recognized by Nigeria's global CSR Consensus Rater (CSRHUB). A total of 504 firm-year observations were considered using the annual reports and accounts of 84 sampled companies. The panel-corrected standard errors (PCSEs) regression was used to test the developed hypotheses for this study. The result of this study documents that economic constraints measured by Access to Finance (ACFI) shows that ACFI is not significantly related to SI. In contrast, COMP is positive and significantly associated with SI. However, the findings also portray that BSZE is negative and significantly associated with SI. At the same time, BOIND significantly and positively influences SI. Similarly, BGD is significant and positively related to SI. On the contrary, BCSRC is negative and insignificantly related to SI. Even though the environmental policy does not moderate the other variables (BSZE, BOIND, and BGD), the finding shows a positive and significant moderating effect of ENVP on the BCSRC and SI. The univariate result of the t-test also shows that SI has substantially improved positively among nonfinancial sector firms than the financial sector. Hence, this study suggests that regulatory authorities should assess how the companies deal with environmental policies in connection with their boards to ensure a good CSR committee that could be responsible for SI practices among firms in Nigeria.